Application of failure mode and effect analysis combined with risk assessment tracking in the management of arthroscopy day surgery instruments (失效模式与效应分析联合风险评估追踪在关节镜日间手术器械管理中的应用) - NI Ting (倪婷); BI Yaxi (毕雅晞); GONG Ronghua (龚荣花) (中西医结合护理)
Objective To explore the effectiveness of failure mode and effect analysis (FMEA) combined with risk assessment tracking in the management of arthroscopic day surgery instruments. Methods To conduct FMEA for each link of arthroscopic day surgery instruments management process, select the failure mode of priority risk value (RPN)> 125, conduct cause analysis, and formulate improvement measures from the aspects of device information tracking, standardized equipment, fine management, and implement risk assessment tracking management. The RPN value, maintenance rate of surgery instruments, accuracy qualification rate of surgical instruments and turnover time of emergency instruments were measured for effectiveness analysis. Results Five major failure modes were determined by FMEA activity, the priority risk values of all major failure modes decreased after activity than before implementation, with a significant difference(P <0. 05). Arthroscopic surgical instruments maintenance rate decreased from 3. 3% to 1. 2%, device accuracy qualification rate increased from 94. 4% to 99. 3%; Emergency instruments turnover time decreased from (204. 14+-12. 85) min to (173. 58+-10. 86) min, with significant difference (P＜0. 05). Conclusion The application of FMEA combined risk assessment and tracking in the arthroscopic day surgical instrument management process can effectively reduce the potential risks, ensure the normal operation of the arthroscopic day surgical instruments, and finally improve the operation efficiency. (目的 探讨失效模式与效应分析 (FMEA) 联合风险评估追踪在关节镜日间手术器械管理中的应用效果。方法 对关节镜日间手术器械管理流程的各个环节进行FMEA, 选出优先风险数值 (RPN)＞125的失效模式, 进行原因分析, 并从器械信息化追踪、标准化配备、精细化管理等方面制定改进措施, 实施风险评估追踪管理。比较FMEA活动前后RPN值、关节镜器械维修率、器械准确合格率及急消器械周转时间, 分析改进效果。结果 通过FMEA活动共确定5项主要失效模式, 活动后各项主要失效模式的优先风险数值均比实施前下降, 差异有统计学意义(P＜0. 05); 关节镜器械维修率由3. 29%降至1. 11%, 器械准确合格率由94. 40%提高至99. 26%, 急消器械周转时间从(204. 14±12. 85) min下降至(173. 58±10. 86) min, 差异均有统计学意义(P＜0. 05)。结论 在关节镜日间手术器械管理流程中应用FMEA联合风险评估追踪可以有效降低潜在风险, 保障关节镜日间手术器械的正常运转, 最终提高手术运行效率, 同时也为关节镜日间手术器械的规范化管理提供参考。)